Efficacy of Long-Term Low-Dose Macrolide Therapy in Preventing Early Recurrence of Nasal Polyps after Endoscopic Sinus Surgery: Long-Term Low-Dose Macrolides and Nasal Polyp Recurrence - Sultan, Muhammad Shouzib; Javaid, Waqas (Pakistan Journal of Health Sciences, 2026)
Long-term low-dose macrolide therapy has been shown to reduce eosinophilic inflammation and delay early recurrence of nasal polyps following endoscopic sinus surgery (ESS). Objective: To compare the efficacy of long-term low-dose macrolide therapy in preventing early recurrence of nasal polyps after endoscopic sinus surgery. Methods: This randomized controlled trial was conducted in the Department of ENT, Sir Ganga Ram Hospital, Lahore, from October to December 2025. Male and female patients aged 15–75 years diagnosed with nasal polyps and undergoing ESS were included. Patients already receiving antibiotics or macrolides, those with multiple facial fractures, or those with neurological or psychological disorders were excluded. Preoperatively, Sino-Nasal Outcome Test (SNOT), Lund-Kennedy endoscopic score, and Lund-Mackay CT score were recorded. Postoperatively, Group A received clarithromycin 250 mg once daily for three months in addition to standard therapy, while Group B received standard postoperative treatment alone. Outcomes were reassessed at 8 and 12 weeks, and recurrence of nasal polyps was evaluated after three months. Results: Mean SNOT scores showed significant improvement in the macrolide group compared to controls at both 8 and 12 weeks (p<0.05). Similarly, Lund-Mackay and Lund-Kennedy scores demonstrated significantly greater reductions in the macrolide group than in the non-macrolide group (p<0.05). Recurrence of nasal polyps was observed in 12% of patients receiving macrolide therapy compared to 32% in the control group. Conclusions: Three-month low-dose clarithromycin therapy (250 mg/day) is a safe and effective adjunct to ESS, significantly improving clinical, endoscopic, and radiological outcomes while reducing early recurrence of nasal polyps.